Bangladesh : Improving the Administration of Civil Service Pensions - World Bank Group (World Bank, Washington, DC, 2018)
As part of a deepening engagement with the Government of Bangladesh (GoB) on the broader pensions agenda, this note analyzes and makes recommendations concerning the administration of civil service pensions. The national social security strategy (NSSS), was launched in 2015 and presented a comprehensive pension reform program towards a universal participatory pension system that is fully funded, covering the elderly and destitute, private sector salaried and informal workers, and public-sector employees. As requested by the GoB, this note supports efforts on this broader agenda with a focused review of the existing administration of civil service pensions, highlighting key areas for improvement. The study looks at the current civil service pension systems and processes, reviewing the use of information technology to transit employees from the payroll to the pension database and assessing the control environment for accounting, payment, and reporting of civil service pensions. Each section highlights key challenges and makes recommendations aimed at strengthening the system. Section one gives introduction. Section two considers civil service pension coverage, budgeting, and administrative arrangements. Section three is focused on improving processing and payment procedures. Section four considers measures to strengthen accounting and monitoring of civil service pensions, and section five concludes.